2009
DOI: 10.1177/1088767909353258
|View full text |Cite
|
Sign up to set email alerts
|

Killings of Police in U.S. Cities since 1980: An Examination of Environmental and Political Explanations

Abstract: Most research on killings of police in urban areas attempted to link lethal violence against officers to the violence and disorder in the communities they work.Yet support for this relationship is inconsistent. Fewer studies considered whether local political arrangements affect killings of police. This study attempts to remedy this gap by using recent data to investigate the relationship between the political conditions of large U.S. cities and the number of homicides of police officers in the line of duty in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 41 publications
(71 reference statements)
2
57
1
Order By: Relevance
“…If the goal is to improve police-citizen interactions, then other strategies should be considered. One in particular concerns improved officer training and higher education standards (Kent 2010). Aside from our work, other studies have found that officer education is important for a number of outcomes, including fewer assaults on police, higher job performance, more flexibility, and fewer citizen complaints (Hayeslip Jr., 1989;Kaminski & Sorensen, 1995;Kappeler et al, 1992;Sterling, 1974).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…If the goal is to improve police-citizen interactions, then other strategies should be considered. One in particular concerns improved officer training and higher education standards (Kent 2010). Aside from our work, other studies have found that officer education is important for a number of outcomes, including fewer assaults on police, higher job performance, more flexibility, and fewer citizen complaints (Hayeslip Jr., 1989;Kaminski & Sorensen, 1995;Kappeler et al, 1992;Sterling, 1974).…”
Section: Discussionmentioning
confidence: 89%
“…Findings in this area are inconsistent, however. For example, median family income, poverty, and unemployment were not associated with killings of police in at least one study (Kent, 2010).…”
Section: Risk Of Violence Against Policementioning
confidence: 91%
See 3 more Smart Citations